2018
DOI: 10.1093/ejcts/ezx476
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of severe mitral valve regurgitation after left ventricular assist device implantation: single-centre observations from a real-life population of patients†

Abstract: Preoperative severe MR resolves in the majority of patients early on after LVAD implantation and is not associated with worse clinical outcomes or intermediate-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…The clinical implications of persistent moderate‐to‐severe MR have been mostly reported in single‐centre studies. However, the prognostic significance of persistent moderate‐to‐severe MR in terms of survival and HF hospitalizations is not consistent across studies 6,8 . In the randomized MOMENTUM 3 trial, patients with HeartMate 3 were less likely to have residual MR at 1 month compared with those with HeartMate II but that residual MR did not impact 2 year mortality 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical implications of persistent moderate‐to‐severe MR have been mostly reported in single‐centre studies. However, the prognostic significance of persistent moderate‐to‐severe MR in terms of survival and HF hospitalizations is not consistent across studies 6,8 . In the randomized MOMENTUM 3 trial, patients with HeartMate 3 were less likely to have residual MR at 1 month compared with those with HeartMate II but that residual MR did not impact 2 year mortality 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Majority of patients have improvement in FMR after LV unloading and positive effects of LV remodelling with long‐term cfLVAD support. Retrospective, single‐centre studies have shown that the incidence of persistent MR after cfLVAD implantation varies from 2.4% to 20% at 6 month follow‐up 6–8 . Recent reports have emerged challenging the conventional belief of ignoring MR at time of cfLVAD implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, single-center studies have demonstrated that post-LVAD implantation residual MR may adversely impact hemodynamics and right ventricular function, whereas others have suggested resolution of severe MR in most cases after LVAD implantation. 5,6 Whether axial or centrifugal continuous-flow LVADs affect MR similarly or differentially is unknown.…”
mentioning
confidence: 99%
“…It is clear now that mitral regurgitation does not resolve in all patients. [3][4][5] Although most patients with preoperative severe mitral regurgitation seem to fare quite well (or even better than those without preexisting severe mitral regurgitation! 6 ) postoperatively, there is some evidence that those with persistent moderate to severe mitral regurgitation after LVAD implantation have a poorer prognosis.…”
mentioning
confidence: 99%